The effect of the perforated pattern on the energy absorption capacity of the steel plate shear wall (Journal of Civil Engineering Researchers, 2022)
In addition to the conventional lateral load resistance system such as different brace system, using of another kind of system that called Steel Plate Shear Wall (SPSW) is extending. Most of the SPSW that used in the construction of the building structure are stiffened by other elements that perpendicular to the frame surface to prevent their buckling. Recent studies show that the performances of this kind of lateral load resistance systems will be improve if the infill plate buckled before the yielding of the surrounding frame. So using of too thick plate is developed that accrued some construction problem and decrease the economic advantage of them. Using of the perforated steel plate shear wall is an applied strategy to remove this problem and lead to the buckle of the infill plate. Using of the perforated steel plate incorporate some confusedness base on the lacking of the code. In this paper 21 number of perforated steel plate shear walls analyzed under cyclic loading by using of the ABAQUS. An appropriate perforated pattern is suggested by study on the hysteresis diagrams. The results show that using of bad pattern reduces the ability of energy absorption and suddenly remove the stability of the SPSW. Otherwise, using of the proper pattern improve the cyclic performance of the perforated steel plate shear wall camper to the other system.
Keywords: Shear wall; Perforated Infill Plates; Low yield steel; Cyclic load